Activist films - WITNESS and its partners
The WITNESS activist films collection consists of 51 documentaries, training and promotional films uncovering violations of human rights and promoting worldwide protection thereof. The collection includes documentaries addressing various human rights issues such as workers’ rights in Asia, youth criminalization in the USA, refugees fleeing armed conflict in Sierra Leone, Uganda and Rwanda among others. Two renowned WITNESS training videos are of special interest: Video for Change, which is available in three languages (English, French and Spanish), and Tips & Techniques, a training video that provides an introduction to the basic skills of shooting video, including lighting, focus, sound, and framing an image. Accruals not expected